HUBUNGAN PENGETAHUAN DAN PERILAKU IBU DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS KALIREJO KECAMATAN NEGERI KATON KABUPATEN PESAWARAN - Akhmad Rokiban; Novita Tri Wahyuni; Anita Purnama Sari (JFL : Jurnal Farmasi Lampung, 2023)
Acute Respiratory Infection (ARI) is an upper or lower respiratory tract disease, where an acute infection process that lasts for 14 days, is caused by microorganisms that attack one or more parts of the respiratory tract, from the nose to the alveoli. This study aims to determine the relationship between knowledge and behavior of mothers with the incidence of ARI in children under five at the Kalirejo Public Health Center Negeri Katon District Pesawaran Regency. This type of research is descriptive observational. This research was conducted in June. The sample in this study was 100 respondents, the sampling technique in this study was accidental sampling, in this study the validity and reliabilitas Based on the chi-square results between knowledge and maternal behavior, a value (p value = 0.020) was obtained, maternal knowledge with the incidence of ARI was obtained (p value = 0.000), maternal behavior with ARI incidence was obtained (p value = 0.041). From this study, it can be concluded that the significance value < 0.05 indicates that there is a relationship between knowledge and maternal behavior, knowledge relationship with the incidence of ARI, and behavior with the incidence of ARI. Keywords: Incidence of ARI, Knowledge, Behavior